London Vet Show 2022 report. (2nd November 2022) - Adams, Vicki
Abstract : The London Vet Show (LVS) took place earlier this month (November 17–18, 2022) — here are the musings of Vicki Adams, who attending on behalf of The Veterinary Nurse, on this year's show. All in all, a good time seemed to have been had by all.